World Bank Group Approach and Action Plan for Climate Change and Health - World Bank Group (World Bank, Washington, DC, 2017)
Climate change (CC) impacts on health outcomes, both direct and indirect, are sufficient to jeopardize achieving the World Bank Group’s visions and agendas in poverty reduction, population resilience, and health, nutrition and population (HNP). In the last 5 years, the number of voices calling for stronger international action on climate change and health has increased, as have the scale and depth of activities. But current global efforts in climate and health are inadequately integrated. As a result, actions to address climate change, including World Bank Group (WBG) investment and lending, are missing opportunities to simultaneously promote better health outcomes and more resilient populations and health sectors. Accordingly, with the financial support of the Nordic Development Fund (NDF), the World Bank Group set out to develop an approach and a 4-year action plan, outlined in this paper, to integrate health-related climate considerations into selected WBG sector plans and investments. The approach and 4-year action plan is to integrate health-related climate considerations into selected WBG sector plans and investments. It does so using the prevailing health sector conceptual framework of Universal Health Coverage, which brings in the positive and negative impacts that investments in other sectors and areas of the economy have on health outcomes. A substantial share of the impacts that climate has on health are mediated through interventions in sectors other than health. Therefore, while reducing GHGs for climate change reasons will generally produce substantial short- and long-term benefits for health, that alone is unlikely to maximize the outcomes of health investments, and in the case of some investments in non-health sectors it may even negatively affect health outcomes. This paper proposes a two-pronged approach. One prong proposes to focus most of the World Bank’s efforts on improving the climate resilience of the health sector, both through purely adaptive solutions but also through improvements to the sector’s sustainable energy access and efficiency. The other prong proposes to look at selected investments in other sectors that affect climate-sensitive health outcomes, to maximize development impact while minimizing the possibility of maladaptation. As such, this paper sets out to inform key groups within the World Bank. It outlines a potential approach for the WBG in climate and health by considering the current health-climate change imperative, the evolution of the global policy environment and the picture today, and global initiatives and WBG roles now and in the future. It also describes strategic objectives and potential operational steps and tools. The underlying premise is that climate affects health today and has the potential to significantly impact global health and poverty reduction in the future, and that there exists a number of options for the WBG and its partner countries to prevent an added burden of illness or death from a changing climate.